The Effects of Succimer and Penicillamine on Acute Lead Poisoning Patients - Dorooshi, Gholamali; Molavi, Negar; Meamar, Rokhsareh; Hasanzadeh, Akbar; Eizadi-Mood , Nastaran (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: Lead poisoning was on the rise in recent years. There exists a lack of easy access to some of the main chelator drugs in developing countries. Thus, this study aimed to explore the comparative effects of Succimer and D-Penicillamine on acute lead poisoning patients from 2013 to 2018. Methods: This descriptive study was conducted in the Clinical Toxicology Department of Khorshid Hospital in Isfahan City, Iran. Adult patients with acute lead poisoning were included in the study. Patients in the 3 treatment groups of D-Penicillamine, D-Penicillamine with succimer, and succimer were compared concerning demographic characteristics as well as clinical and laboratory findings at admission time and two weeks later. Results: In total, 163 patients were evaluated in this research. There was no significant difference between the treatment groups respecting improvement in clinical symptoms. The mean blood lead levels during hospitalization and two weeks after the treatment did not significantly differ between the three groups; however, there was a significant reduction in all study groups after two weeks of treatment (P<0.05). The mean white blood cell count was significantly lower only in the D-Penicillamine group two weeks after hospitalization (P<0.05). In the D-Penicillamine group, the mean platelet, hematocrit, and hemoglobin levels were significantly lower two weeks after hospitalization, although within the healthy range. Conclusion: D-Penicillamine may be an acceptable chelator drug for treating patients with acute lead poisoning, especially in communities without access to drugs, like succimer.